In Vitro and In Vivo Evaluation of 99mTc-Polymyxin B for Specific Targeting of Gram-Bacteria - Sveva Auletta; Filippo Galli; Michela Varani; Giuseppe Campagna; Martina Conserva; Daniela Martinelli; Iolanda Santino; Alberto Signore (Biomolecules, 2021)
Background: Infectious diseases are one of the main causes of morbidity and mortality worldwide. Nuclear molecular imaging would be of great help to non-invasively discriminate between septic and sterile inflammation through available radiopharmaceuticals, as none is currently available for clinical practice. Here, we describe the radiolabeling procedure and in vitro and in vivo studies of 99mTc-polymyxin B sulfate (PMB) as a new single photon emission imaging agent for the characterization of infections due to Gram-negative bacteria. Results: Labeling efficiency was 97 ± 2% with an average molar activity of 29.5 ± 0.6 MBq/nmol. The product was highly stable in saline and serum up to 6 h. In vitro binding assay showed significant displaceable binding to Gram-negative bacteria but not to Gram-positive controls. In mice, 99mTc-HYNIC-PMB was mainly taken up by liver and kidneys. Targeting studies confirmed the specificity of 99mTc-HYNIC-PMB obtained in vitro, showing significantly higher T/B ratios for Gram-negative bacteria than Gram-positive controls. Conclusions: In vitro and in vivo results suggest that 99mTc-HYNIC-PMB has a potential for in vivo identification of Gram-negative bacteria in patients with infections of unknown etiology. However, further investigations are needed to deeply understand the mechanism of action and behavior of 99mTc-HYNIC-PMB in other animal models and in humans.